2017
DOI: 10.1021/acsami.6b15400
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quaternary Ammonium Salts Based on Diketopyrrolopyrroles Skeletons and Their Applications in Copper Electroplating

Abstract: A series of DPP derivatives bearing quaternary ammonium salt centers with different lengths of carbon chains have been designed and synthesized. Their inhibition actions on copper electroplating were first investigated. A total of four diketopyrrolopyrrole (DPP) derivatives showed different inhibition capabilities on copper electroplating. To investigate interactions between metal surface and additives, we used quantum chemical calculations. Static and dynamic surface tension of four DPP derivatives had been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Hence, the surfactivity of additives were closely related to the ability of inhibiting copper electrodeposition. Our previous study has shown that the compound with the lowest surface tension indicated the strongest inhibition of copper electrodeposition . Compared with the lowest surface tension (47.1 m Nm −1 ) of the DPP‐based quaternary ammonium salt in our previous work, the lowest surface tension of the compound 1 e reached 19.7 m Nm −1 .…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Hence, the surfactivity of additives were closely related to the ability of inhibiting copper electrodeposition. Our previous study has shown that the compound with the lowest surface tension indicated the strongest inhibition of copper electrodeposition . Compared with the lowest surface tension (47.1 m Nm −1 ) of the DPP‐based quaternary ammonium salt in our previous work, the lowest surface tension of the compound 1 e reached 19.7 m Nm −1 .…”
Section: Resultsmentioning
confidence: 59%
“…During the practical plating process, the new liquid‐solid interface is constantly forming and the surface tension is never balanced . An inhibition effect of additive molecules was required to reach the liquid‐solid interface on copper electrodeposition .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations